The Effect of Leaf Area on Transpiration Rate in Various Types of Tropical Leaf Plants in Open Environments - Artanti, Nabilah; Rianti, Farah; Septianingrum, Beatrix Putri; Khairurohmah, Dinda; Ramadani, Aida Lutfia; Yahya, Leoni Agustiyar Nur; Marianingsih, Pipit (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The rate of transpiration in plants is affected by morphological characteristics and environmental conditions. This research aimed to examine how leaf surface area influences the transpiration rate of three tropical plant species: taro (Colocasia esculenta), starfruit (Averrhoa carambola), and water guava (Syzygium aqueum). The study measured the initial and final mass of leaves over a defined observation period to calculate the transpiration rate per unit area. Findings indicated that taro leaves exhibited the highest transpiration rate (0.0628 mg·cm⁻²·min⁻¹), followed by starfruit (0.0481 mg·cm⁻²·min⁻¹), while water guava recorded the lowest value (0.0350 mg·cm⁻²·min⁻¹), despite its relatively large leaf area. These results suggest that leaf area alone is not the primary determinant of transpiration rate; other factors such as cuticle thickness, stomatal density, and environmental parameters (including humidity, temperature, and light intensity) also play significant roles. Future research is recommended to explore a wider range of plant species and controlled environmental conditions to achieve more comprehensive insights.